Pengaruh Ukuran Partikel Dan Waktu Kontak Terhadap Penyisihan Zat Organik Dan Mangan (Mn) Pada Air Gambut Menggunakan Tanah Lempung Gambut Yang Diaktivasi Asam Sulfat Sebagai Adsorben - Nurul Rahmatika Putri; Syarfi Daud; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Domestic wastewater contributes greatly to water pollution in urban areas because the application Peat water contains high levels of Mn, Fe and organic substances. If used continuously for a long time can cause negative impacts such as health problems so it needs special processing in order to become clean water. This study aims to determine the influence of particle size and contact time on the efficiency of allowance of organic and manganese substances (Mn) in peat water as well as adsorption capacity in the adsorption process using chemically activated peat clay soil with sulfuric acid as an adsorbent. The study varied the size of adsorbent particles -20 +40, -60 +80 and -80 +100 mesh with adsorbent mass of 6 gr/L and contact time variations of 120, 140 and 160 minutes with stirring speed of 150 rpm. The results showed the allowance of organic substances and manganese (Mn) was best obtained at adsorbent particle size -80 +100 mesh and contact time of 160 minutes with an organic substance allowance efficiency value of 85.31% and manganese (Mn) of 82.27%. The best adsorption capacity is achieved at -80 +100 mesh particle size and 160 minutes contact time with organic substance adsorption capacity value of 61.58 mg/g and manganese (Mn) of 0.099 mg/g.Keywords: Peat Water, Peat Clay Soil, Adsorption, Chemical Activation, Organic Substances and Manganese (Mn)